Status Gizi Ibu Hamil Kejadian Bayi Berat Badan Lahir Rendah (BBLR) Di Wilayah Puskesmas Karangmoncol Tahun 2024 - anita, anita (2024)
Pregnant women with nutritional problems, namely Chronic Energy Deficiency (CED), have a serious impact on the health of the pregnant woman herself and the baby she is carrying because they are at risk of giving birth to a baby with LBW. The purpose of this study was to analyze the relationship between the nutritional status of pregnant women and the incidence of Low Birth Weight Babies in the Karangmoncol Health Center area. The research method is non-parametric comparative analytic with a retrospective cross-sectional research design. The population in this study were all postpartum mothers recorded in the KIA cohort of pregnant women at the Karangmoncol Health Center in 2023, selecting case samples with simple random sampling according to inclusion and exclusion criteria, data management was carried out statistically using univariate analysis and biavariate analysis with the Chi-Square test. The results of the study showed that the nutritional status of pregnant women who did not experience KEK was 33 respondents (55%) while those who experienced KEK were 27 respondents (45%) and there were 24 respondents (40%) of LBW cases, 36 respondents (60%) of non-LBW cases and there was a relationship between maternal nutritional status and the incidence of low birth weight (LBW) with a p-value of 0.000. The conclusion of this study is that there is a relationship between the relationship between maternal nutritional status and the incidence of low birth weight (LBW) in the Karangmoncol Health Center area.